PENGARUH ANGGARAN TERHADAP KINERJA MANAJERIAL: KOMITMEN ORGANISASI, GAYA KEPEMIMPINAN, LOC SEBAGAI MODERATOR - Tambunan, Widya Novita Berliana; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to test the influence of budget participation to the managerial performance through organization commitment, leadership style, and locus of control at PT PAL Indonesia (PERSERO). This research has been carried out by using survey method and questionnaires have been issued to 70 respondents and only 60 questionnaires of the respondents return. The respondents are all staffs of PT. PAL Indonesia (PERSERO). The sample collection has been done by using total sampling technique method. The analysis technique has been done by using Moderated Regression Analysis (MRA). This research is a quantitative research which focuses on the first hypothesis test which shows that budget participation has an influence to the managerial performance which shows that H1 is accepted which means that budget participation has an influence to the managerial performance. Meanwhile, the second hypothesis shows that H2 is not significant and it can moderate the correlation between budget participation and managerial performance.Keywords: Budget Participation, Organization Commitment, Leadership Style, Locus of Control, Managerial Performance.